WTO and the Greater China : Economic Integration and Dispute Resolution. - Wu, Chien-Huei (Nijhoff international trade law series., 2012)
Focusing on the impact of WTO disciplines, this book explores the WTO's contribution to domestic reform, economic integration and dispute settlement of China, Taiwan, Hong Kong and Macau: the four WTO Members in Greater China.